SCENARIOS FOR THE DEVELOPMENT OF A DIGITAL UNIVERSITY IN THE CONTEXT OF EDUCATIONAL TRANSFORMATION - Наталія Бобро (Економіка та суспільство)
The article is devoted to the topical issues of the development of a digital university in the context of educational transformation and the digitalization of society. The author determines that one of the promising ways to modernize the system of professional education is to create and develop digital educational platforms, which are integrated information system focused on the implementation of mutually beneficial interactions of independent participants in the educational process using modern digital technologies. Based on the analysis of the component structure of digital platforms - education, digitalization, and platform - the key features and economic nature of each element are identified. The author substantiates and systematizes six main scenarios for the development of digital universities depending on the type of initial resource provision: based on companies that do not belong to the educational or IT industries; companies from the IT sphere; specialized companies that initially position themselves in the field of EdTech; companies that transform digital services into an educational platform; based on network educational organizations and through the creation of consortia of educational institutions. Keywords: digital university,